Komodifikasi Budaya Lokal dalam Televisi: Studi Wacana Kritis Komodifikasi Pangkur Jenggleng - Mr Sumanri (Program Studi Ilmu Komunikasi, 2011)
Pangkur Jenggleng is a kind of Macapat, traditional song of Java. It was packaged as a cultural art program in RRI Nusantara II Yogyakarta in the era of 1960S-1970S. Then, it was repackaged by TVRI Yogyakarta and sponsored by Amien Rais Information Center using stage comedy format in 2003. The changing of media format from audio to audiovisual -with any adjustment- make a shift in the value of the meaning of Pangkur Jenggleng. Accentuation of humor in Pangkur Jenggleng TVRI changes cultural value from traditional to mass culture. This phenomenon is not only seen as a media format adjustment, but also as a form of commodification. The research attempts to seek form, process, ideology, and power behind the commodification of Pangkur Jenggleng.